European Climate Pact Ambassadors as New Organic Intellectuals: Neo-Gramscian Analysis of EU Climate Hegemony and Just Transition - Mihail Caradaică (Romanian Journal of European Affairs)
Using a neo-Gramscian theoretical framework, this paper assumes that European Climate Pact Ambassadors (CPAs) play an essential role in the European green transition, thus contributing to defining new climate hegemony within the EU. The research question answered by the present paper is whether these climate ambassadors can be understood as “organic intellectuals” (in the sense forwarded by Antonio Gramsci) for their participation in the construction of a counter-hegemonic discourse and their determination to challenge the traditional modes of a fossil fuel-based economy. As such, these ambassadors will be ideally placed to develop a new narrative for climate action based on the just transition to the ambitious objectives of the European Green Deal. From this perspective, the article contributes to the broader debate on climate governance by sharply underlining the necessity of grassroots involvement and the possibility offered through a neo-Gramscian analysis to understand the dynamics of climate hegemony in the EU.